Does 'Grease Money' Speed Up the Wheels of Commerce? - Kaufmann, Daniel (IMF Working Papers; Working Paper ;, 2000)
In a general equilibrium in which bribe-extracting bureaucrats can endogenously choose regulatory burden and delay, the effective (not just nominal) red tape and bribery can be positively correlated across firms. Using data from three worldwide firm surveys, this paper finds evidence consistent with this hypothesis. Firms that pay more in bribes are also likely to spend more, not less, management time with bureaucrats in negotiating regulations. They also face a higher, not lower, cost of capital.